Microsatellite instability status differentially associates with intratumoral immune microenvironment in human cancers. Issue 3 (22nd August 2020) - Zhang, Peng; Liu, Mingyue; Cui, Ya; Zheng, Pan; Liu, Yang
Abstract: Based on clinical outcomes in colorectal cancer, high microsatellite instability (MSI-H) has recently been approved by the Food and Drug Administration (FDA) as a genetic test to select patients for immunotherapy targeting PD-1 and/or CTLA-4 without limitation to cancer type. However, it is unclear whether the MSI-H would broadly alter the tumor microenvironment to confer the therapeutic response of different cancer types to immunotherapy. To fill in this gap, we performed an in silico analysis of tumor immunity among different MSI statuses in five cancer types. We found that consistent with clinical responses to immunotherapy, MSI-H and non-MSI-H samples from colorectal cancer (COAD-READ) exhibited distinct infiltration levels and immune phenotypes. Surprisingly, the immunological difference between MSI-H and non-MSI-H samples was diminished in stomach adenocarcinoma and esophageal carcinoma (STAD-ESCA) and completely disappeared in uterine corpus endometrial carcinoma (UCEC). Regardless of cancer types, the abundance of tumor-infiltrating immune cells, rather than MSI status, strongly associated with the clinical outcome. Since preexisting antitumor immune response in the tumor (hot cancer) is accepted as a prerequisite to the therapeutic response to anti-PD-1/CTLA-4 immunotherapy, our data demonstrate that the impact of MSI varied on immune contexture will lead to the further evaluation of predictive immunotherapy responsiveness based on the universal biomarker of MSI status.